Solo Oud Accompaniment Iraqi singing (Journal of the College of Basic Education, 2022)
The research consists of four chapters with a list of sources and appendices as follows:The first chapter deals with the methodological framework of the research, as it begins with presenting the research problem that sheds light on the fame of the people of Iraq since ancient times for the delicacy of their feelings, the accuracy of their thought, and their good description of the nature and environment in which they live, as music and singing occupy a distinguished place in the culture and heritage of its inhabitants, and the oud instrument was found as a musical instrument since The Akkadian era (2350-2170 BC), when it was affiliated with singing, and today it is either a means of melodic construction or an accompaniment (translated) to it.